Typical investigative situations in the initial phase of a war-related sexual violence investigation - O. O. Naumkin (Bulletin of Kharkiv National University of Internal Affairs)
A comparative analysis of scientific provisions regarding the phasing of the pretrial investigation process and the content of the concept of “investigative situation” has been conducted. The essence and meaning of the specified scientific abstraction has been revealed.